The effects of an 8-week off-season period on the mechanical properties of sprinting in professional rugby league players: implications for training recommendations - Dobbin, N.; Clarke, J.; Cushman, S. (Journal of Trainology, 2020)
Objective: To determine the change in mechanical properties of sprinting performance across an 8-week off-season period in professional rugby league players. Design: Repeated measures Methods: Twenty-six professional rugby league players from a single rugby league team competing in Super League completed two assessments of linear sprint performance during final week of the season and second week of preseason. Linear split times were used to model the horizontal force-velocity profile and determine theoretical maximal force (F0), velocity (V0) and power (Pmax). Results: Our result indicated moderate-to-large increases in split times at each distance across the off-season period (ES = 0.86 to 1.24; most likely), indicative of a reduced sprinting ability. Furthermore, small reductions in F0 (ES -0.34 to -0.57; likely to very likely) were observed, whilst the reduction in V0 (ES = -0.81; most likely) and Pmax (ES = -0.62 to -1.03; most likely) were considered moderate in magnitude. Conclusions: An 8-week off-season period elicited negative changes in linear sprint times and the horizontal force-velocity profile of professional rugby league players. Such findings might have implications for preseason training loads and therefore, the off-season period requires careful consideration by practitioners and clinicians with regards to content and monitoring.